A class of super dense stars models using charged analogues of Hajj-Boutros type relativistic fluid solutions - Pant, Neeraj; Pradhan, Nirakar; Murad, Mohammad Hassan (© 2014, Springer Science+Business Media New York, 2016)
This article was published in the International Journal of Theoretical Physics [© 2014, Springer Science+Business Media New Yor] and the definite version is available at : http://dx.doi.org/10.1007/s10773-014-2147-0. The Journal's website is at: http://link.springer.com/article/10.1007%2Fs10773-014-2147-0